Prophetic Journalism in the Context of Local Media: Formulation, Dynamics, and Response - Lukman Hakim; Ghulam Falach (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2026)
The demand for speed in delivering news online often causes journalists to sacrifice accuracy and ethical standards. Therefore, prophetic journalism emerges as a paradigm that emphasises prophetic values. This study aims to identify how Kediripedia.com implements these values and how the platform leverages opportunities and faces challenges to maintain journalistic quality. A constructivist paradigm and qualitative approach were employed to collect data through interviews, observation and documentation, which were then analysed using Teun A. van Dijk’s three-dimensional Critical Discourse Analysis. The findings reveal that Kediripedia.com successfully integrates prophetic journalism values into its editorial practices and news products. Shiddiq (truthfulness) is reflected in editorial honesty; Amanah (trustworthiness) in the team’s moral responsibility; Tabligh (communication) in the use of a distinctive storytelling style; and Fathanah (wisdom) in the broad interpretation of local issues. Challenges such as financial pressure, maintaining integrity and competing with other digital media are addressed through content diversification, community collaboration and developing a unique audience segmentation strategy, which strengthens Kediripedia.com’s position as a local media platform.